ChemInform Abstract: Application of X‐Ray Resonant Diffraction to Structural Studies of Liquid Crystals. Issue 26 (6th June 2013) - Barois, P.; Gleeson, H.; Huang, C. C.; Pindak, R.
Abstract Review: 39 refs.